Usaha Tani Rumput Laut dalam Meningkatkan Perekonomian Keluarga Perspektif Ekonomi Islam - Ismail; Syafrudin; Rafiuddin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to uncover how the Waduruka community plays a role in improving family economy through seaweed farming and how Islamic economics views seaweed farming in enhancing family economy. Seaweed farming is considered labor-intensive, thus capable of absorbing labor. The future development of the seaweed processing industry has very bright prospects in terms of creating economic growth (pro-growth), increasing employment opportunities (pro-employment), and reducing poverty in the country (pro-poor). The research method used is qualitative research with primary and secondary data. Data collection techniques include interviews, observation, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing or verification. Meanwhile, the data credibility test used is triangulation, and references are used. The study's results reveal that family income from seaweed farming shows better income, as seaweed can be diligently managed and properly handled to penetrate the national market. Additionally, the researchers found the practice of combining sale and purchase contracts with debt between farmers (mudharib) and collectors as financiers (shahibul maal), which is prohibited (haram). The results of this study contribute as information and input of thought. The limitation of this study is the lack of data, which is still limited to primary and secondary data. Future research needs to use quantitative data.